PENINGKATAN KEMAMPUAN MENULIS NASKAH DRAMA MELALUI PEMBELAJARAN BERBASIS BRAIN BASED LEARNING PESERTA DIDIK KELAS IXF SMP NEGERI 2 CAMPALAGIAN - Muthmainnah Muthmainnah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2016)
This study is Classroom Action Research design and conducted at SMP Negeri 2 Campalagian which aims to describe the ability of writing drama script IXF grade students of SMP Negeri 2 Campalagian through brain-based learning. The subjects were pessrta IXF grade students of SMP Negeri 2 Campalagian the school year 2015/2016 as many as 28 (16 male and 12 female) students. Data collection techniques used is the calculation of the average value of learners from the initial value, the first cycle and the second cycle. Results obtained on the average value of early learners ie 64 or by 17.92%, based on preliminary analysis that shows that the ability of learners the ability to write plays that are in the low category. The first cycle that learners are categorized finished with an average value of 67.64, learners who completed as many as 11 people or 39.28%, and the second cycle students who are categorized finished with an average value of 84.85, learners were completed by 28 or by 100%. This shows that an increasing ability to write drama script on IXF grade students of SMP Negeri 2 Campalagian during the learning process by using brain-based learning.